2019
DOI: 10.3389/fpsyg.2019.01256
|View full text |Cite
|
Sign up to set email alerts
|

Unique Predictors of Sleep Quality in Junior Athletes: The Protective Function of Mental Resilience, and the Detrimental Impact of Sex, Worry and Perceived Stress

Abstract: Since athletic development and functioning are heavily dependent on sufficient recuperation, sleep in athletes is becoming a topic of increasing interest. Still, existing scientific evidence points to inadequate sleep in athletes, especially in females. This may be due to the fact that sleep is vulnerable to disturbances caused by stress and cognitive and emotional reactions to stress, such as worry and negative affect, which may exacerbate and prolong the stress response. Such disturbing factors are frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
(91 reference statements)
5
20
1
Order By: Relevance
“…Our research showed that education levels were positively correlated with sleep quality, while age, gender, and marital status had negative impacts on sleep quality. These finding were consistent with previous research ( Bote et al, 2006 ; Hrozanova et al, 2019 ). For instance, in the investigation conducted by Hrozanova et al (2019) , the female gender accounted for approximately 2% of the variance for poor quality of sleep, which may be caused by the general experience of worry and stress of women ( Matud, 2004 ; Hrozanova et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our research showed that education levels were positively correlated with sleep quality, while age, gender, and marital status had negative impacts on sleep quality. These finding were consistent with previous research ( Bote et al, 2006 ; Hrozanova et al, 2019 ). For instance, in the investigation conducted by Hrozanova et al (2019) , the female gender accounted for approximately 2% of the variance for poor quality of sleep, which may be caused by the general experience of worry and stress of women ( Matud, 2004 ; Hrozanova et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
“…Evidence from previous research has indicated that both of the two forms of psychological resilience positively predicted sleep quality. As an ability or trait, sleep disorders could be reduced by resilience-improving training in junior athletes ( Hrozanova et al, 2019 ). As a positive psychological outcome or adaptation process, individuals could decrease sleep disorders by adjusting and adapting this prosses among left-behind children ( Yao, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results of our study reveals that perceived stress might not only exert a direct effect on burnout, but could also have indirect effect on burnout through sleep quality, indicating that nurses with higher levels of perceived stress tend to report poorer sleep quality and there is an increased risk on the development of burnout. This finding confirms previous studies revealing the positive correlation between perceived stress and poor sleep quality (58,59). A possible explanation might be that sleep has been revealed to play a vital role in restoring daily functioning and regulating emotional experiences, which could mediate the relationship between stress and negative effects of burnout and help the brain process emotionally stressful events in adaptive ways (60).…”
Section: Discussionsupporting
confidence: 90%
“…Poor sleep in athletes may reflect sport-specific demands, such as challenging organizational, competitive ( Hanton et al, 2005 ), and psychophysiological stressors ( Nixdorf et al, 2015 ; Campbell et al, 2018 ). Indeed, previous research has established that sleep of athletes may be negatively influenced by increases in training load ( Kolling et al, 2016 ) and early morning scheduling of training sessions ( Sargent et al, 2014 ) and matches ( Juliff et al, 2015 ) as well as psychological aspects (e.g., worry) of the stress response ( Hrozanova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…During competition, sleep onset latency is found to increase, and sleep quality deteriorates, likely due to stress-related cognitive activity associated with competing ( Lastella et al, 2014 ; Juliff et al, 2015 ). One large cross-sectional study identifies perceived stress as the most important predictor of poor sleep quality ( Hrozanova et al, 2019 ). Regarding the effects of sleep on mental functioning in athletes, another cross-sectional study finds associations between poor sleep quality and confusion, depression, and fatigue ( Andrade et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%